Diagnosis telling in people with psychosis - Milton, A.; Mullan, Barbara (Lippincott Williams & Wilkins, 2014)
Purpose of review: There are complexities in communicating diagnostic information relating to schizophrenia spectrum disorders. There is a current dearth of research in understanding how clinicians effectively communicate with service users about such diagnostic news. In this review, we aim to synthesize the latest research throughout 2012 and 2013 that presented data relating to the communication of a diagnosis of schizophrenia spectrum disorders, including individuals who had experienced first-episode psychosis or were in at-risk mental states. Comprehensive database and manual searches were conducted which obtained data from both service users and health professional groups. Recent findings: Fourteen quantitative and qualitative studies were found. The majority of studies were descriptive and heterogeneous in content. Key themes included service user preferences towards disclosure and diagnostic terminology, health professional training, stigma-related issues and the use of diagnostic communication models. Summary: Overall, communication models that foster therapeutic relationships and actively encourage the health professional to reduce stigma may be a key to initial diagnostic discussions in clinical practice. Such communication models and intervention require further more rigorous evaluation, as none have been tested through randomized controlled protocols in clinical settings.